2009
DOI: 10.1016/j.sbi.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase fidelity and transcriptional proofreading

Abstract: Whereas mechanisms underlying the fidelity of DNA polymerases (DNAPs) have been investigated in detail, RNA polymerase (RNAP) fidelity mechanisms remained poorly understood. New functional and structural studies now suggest how RNAPs select the correct nucleoside triphosphate (NTP) substrate to prevent transcription errors, and how the enzymes detect and remove a misincorporated nucleotide during proofreading. Proofreading begins with fraying of the misincorporated nucleotide away from the DNA template, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
133
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(144 citation statements)
references
References 90 publications
3
133
1
2
Order By: Relevance
“…This observation highlights the importance of the network of contacts that exist in the closed conformation of the enzyme between the incoming NTP and the TL/BH unit and how these interactions can either assist or hinder the folding of the TL necessary for elongation. This mechanism also suggests a role of the TL in fidelity control as has been proposed (4,7,10,34,46,59). Fig.…”
Section: Discussionsupporting
confidence: 68%
“…This observation highlights the importance of the network of contacts that exist in the closed conformation of the enzyme between the incoming NTP and the TL/BH unit and how these interactions can either assist or hinder the folding of the TL necessary for elongation. This mechanism also suggests a role of the TL in fidelity control as has been proposed (4,7,10,34,46,59). Fig.…”
Section: Discussionsupporting
confidence: 68%
“…It was suggested that the elemental pause is characterized by fraying of the 3′-terminal RNA nucleotide away from the DNA template [103]. Structural analysis showed that RNA fraying can occur, as a frayed RNA 3′-nucleotide was observed in a Pol II EC crystal with a mismatched base pair at the end of the hybrid [104,105]. The frayed 3′-nucleotide was found in two alternative sites that overlap with the NTP-binding site, explaining how nucleotide addition is prevented in the elemental pause state.…”
Section: Pausing and Proofreadingmentioning
confidence: 99%
“…2). As a result of structural and biochemical work from several research groups [104,[106][107][108][109][110], a model for transcriptional proofreading has emerged (reviewed in [105]). After nucleotide misincorporation, the mismatched 3′-nucleotide does generally not form a stable nascent base pair at register + 1 but may rather fray away from the DNA template, inducing a paused state and inhibiting RNA extension.…”
Section: Pausing and Proofreadingmentioning
confidence: 99%
“…Interestingly, GPN proteins have also been demonstrated to interact with the CCT complex, which controls the polymerization of tubulins into microtubules (9). Since the nuclear import of several nuclear proteins has been previously reported to be regulated by the CCT complex, these findings let the authors speculate that there is a possible physiological link between the GPN1 and GPN3 interactions and the import of RNAPII into the nucleus.…”
mentioning
confidence: 96%